Bioefficacy Evaluation of Commercial Mosquito Coils Containing Metofluthrin, d-Allethrin, d-Trans Allethrin, and Prallethrin Against Aedes albopictus (Diptera: Culicidae) in Malaysia - Chen, Chee Dhang; Chin, A.C.; Lau, Koon Weng; Low, Van Lun; Lee, Han Lim; Lee, P.K.Y.; Azidah, Abdul Aziz; Sofian-Azirun, Mohd (Oxford University Press, 2018)
The bioefficacy of commercial mosquito coils containing four different active ingredients, namely metofluthrin, d-allethrin, d-trans allethrin, and prallethrin against Aedes albopictus (Skuse) (Diptera: Culicidae) from 10 states in Malaysia, was evaluated using the glass chamber method. In this study, Ae. albopictus exhibited various knockdown rates (50% knockdown time, KT 50 ), ranging from 2.50 to 5.00 min, 2.50 to 7.00 min, 3.00 to 8.00 min, and 5.00 to 17.00 min for metofluthrin, d-trans allethrin, d-allethrin, and prallethrin, respectively. Overall, all strains of Ae. albopictus were most susceptible to metofluthrin, with mortality rates >80%. On the other hand, mortality rates ranging from 5.0 to 100% were observed from all populations exposed to d-trans allethrin, d-allethrin, and prallethrin. In addition, significant correlations between KT 50 of metofluthrin and d-allethrin (r = 0.758, P = 0.011), metofluthrin and prallethrin (r = 0.676, P = 0.032), d-allethrin and d-trans allethrin (r = 0.832, P = 0.003), d-allethrin and prallethrin (r = 0.921, P = 0.000), and d-trans allethrin with prallethrin (r = 0.941, P = 0.000) were detected, suggesting some levels of cross-resistance within the pyrethroid insecticides. This study demonstrated that metofluthrin can induce high insecticidal activity in Ae. albopictus in Malaysia, followed by d-trans allethrin, d-allethrin, and prallethrin.